An extended chemical index model to predict the fly ash dosage necessary for mitigating alkali–silica reaction in concrete. (April 2016) - Gholizadeh Vayghan, Asghar; Wright, Jared Robert; Rajabipour, Farshad
Abstract: Currently, the concrete prism test per ASTM C1293 or RILEM AAR-3 is considered the most reliable accelerated test to determine the dosage of pozzolans to suppress alkali–silica reaction (ASR) in concrete. However, the test takes 2 years, which makes it impractical as a mixture design tool for new concrete construction. In the present work, a multiple nonlinear regression model is developed for predicting the fly ash dosage necessary to mitigate ASR per CPT. The model uses the oxide compositions of Portland cement and fly ash as well as the reactivity of the aggregates. Seventy-six experimental data points on CPT expansion results for plain Portland cement and fly ash-blended concrete mixtures were used to develop and evaluate the model. The model successfully predicts the fly ash required to mitigate ASR for different aggregates, cement, and fly ash combinations. The prediction errors in most cases meet ASTM C1293 multi-laboratory precision criterion.